Autosomal Dominant Alternating Hemiplegia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
The familial occurrence and autosomal dominant inheritance of alternating hemiplegia of childhood is reported from Children's Hospital, and Massachusetts General Hospital, Harvard Medical School, Boston.